Development of reference intervals for pupillometry in healthy dogs - Mills, Erinn P.; Combs-Ramey, Kelli; Kwong, Grace P. S.; Pang, Daniel S. J. (Frontiers in Veterinary Science, 2022)
Background: Pupillometry, the measurement of pupil size and reactivity to a stimulus, has various uses in both human and veterinary medicine. These reflect autonomic tones, with the potential to assess nociception and emotion. Infrared pupillometry reduces inaccuracies that may occur when the pupillary light reflex is determined subjectively by the examiner. To our knowledge, there are no published studies outlining normal reference intervals for automated pupillometry in dogs. Objective: The objective of this study was to develop de novo automated pupillometry reference intervals from 126 healthy canine eyes. Methods: The pupillary light reflex (PLR) was measured with a handheld pupillometer (NeurOptics PLR-200 Pupillometer). Parameters recorded included maximum pupil diameter (MAX), minimum pupil diameter (MIN), percent constriction (CON), latency (LAT), average constriction velocity (ACV), maximum constriction velocity (MCV), average dilation velocity (ADV) and time to 75% pupil diameter recovery (T75). One measurement was obtained for each eye. Results: The following reference intervals were developed: MAX (6.05 – 11.30 mm), MIN (3.76 – 9.44 mm), CON (-37.89 – -9.64 %), LAT (0.11 – 0.30 s), ACV (-6.39 – -2.63 mm/ s), MCV (-8.45 – -3.75 mm/s), ADV (-0.21 – 1.77 mm/s), and T75 (0.49 – 3.20 s). Clinical Significance: The reference intervals developed in this study are an essential first step to facilitate future research exploring pupillometry as a pain assessment method in dogs.